The Association between Internalizing Symptoms and Witnessing School Bullying and Defending Behavior: An Analysis of Gender Differences among Elementary and Middle School Students - Diana M. Doumas; Aida Midgett; Matt Peck (MDPI AG, 2023)
Bullying is a significant public health concern that begins as early as elementary school and peaks in middle school. Although researchers have demonstrated the relationship between internalizing symptoms and being a target of bullying, there is limited research examining the association between internalizing symptoms and witnessing school bullying and defending targets or gender differences in these relationships. In this cross-sectional study, we examined gender as a moderator of the relationships between internalizing symptoms (e.g., depressive symptoms and social anxiety) and witnessing school bullying and defending behavior in a sample of elementary and middle school students (N = 126; 51.6% female; 3rd-8th grade). Results demonstrated that witnessing school bullying was a significant predictor of depressive symptoms. For social anxiety, the gender x witnessing school bullying interaction was significant for social avoidance and distress (SAD), such that among female students, SAD was positively related to witnessing school bullying. In contrast, the gender x defending behavior interaction was significant for fear of negative evaluation (FNE), such that among male students, FNE was positively related to defending behavior. Findings suggest bullying prevention should incorporate bystander training programs that include a focus on gender differences in social anxiety associated with being a bullying bystander.